Environmental Assessment: Integration of Carbon Footprint - Obrecht, Matevž (Mastering Sustainability in Supply Chains, 2026)
Due to the rise in population numbers the standard of living and the subsequent growth in human activities and production, environmental concern is intensifying and the current linear economy is becoming unsustainable. The idea of an environmentally conscious (green) supply chain management first began in the early 1970s; however, a systematic approach is still lacking today. The focus of this chapter is therefore to gain a clearer insight into environmental assessment for efficient greening of supply chains, to raise importance of the life cycle thinking and decarbonisation and to study and discuss the use of methods for environmental impact assessment. Comprehensive assessment of environmental impacts is crucial for supply chain managers to enable them to better understand the importance of environmentally sound business models while also emphasising sustainable development for the resilient future of decarbonisation since human activities are a major contributor of carbon dioxide and other greenhouse gases. Carbon footprint identifies and measures the impact and enables systematic minimisation of emissions from company's processes and business.